2003
DOI: 10.1634/theoncologist.8-4-375
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic Thrombocytopenic Purpura Associated with Bone Marrow Metastasis and Secondary Myelofibrosis in Cancer

Abstract: To examine the relationship between cancer and development of thrombotic microangiopathy (TM), the medical records of patients with known TM were examined in one institution from January 1981 to December 2002. Nine out of 93 patients with the established diagnosis of TM had active cancer. All nine of those patients had thrombotic thrombocytopenic purpura (TTP). Among those patients, two patients received chemotherapy prior to the development of TTP. Six of the seven patients who received no chemotherapy had ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
3
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 44 publications
3
29
3
1
Order By: Relevance
“…In pulmonary tumor TMA, a rare entity causing severe pulmonary hypertension in patients with disseminated malignancies [28,29], it was suggested that tissue factor and vascular endothelial growth factor, by inducing fibrin deposits and vascular hyperplasia, respectively, may be involved in the occlusion or stenosis of the pulmonary vasculature [30,31]. Additionally, malignant cells may produce substances favoring TMA, such as mucins [8]. By favoring vasoconstriction and endothelial cell apoptosis, tumor necrosis factor-␣ may have a role in the occurrence of TMA in patients with cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…In pulmonary tumor TMA, a rare entity causing severe pulmonary hypertension in patients with disseminated malignancies [28,29], it was suggested that tissue factor and vascular endothelial growth factor, by inducing fibrin deposits and vascular hyperplasia, respectively, may be involved in the occlusion or stenosis of the pulmonary vasculature [30,31]. Additionally, malignant cells may produce substances favoring TMA, such as mucins [8]. By favoring vasoconstriction and endothelial cell apoptosis, tumor necrosis factor-␣ may have a role in the occurrence of TMA in patients with cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…TTP is generally idiopathic, and the association with adenocarcinomas is extremely infrequent [1,2].We report a case of a 69-year-old woman with TTP syndrome secondary to metastatic cancer and normal ADAMTS13 (von Willebrand factor [vWf]-cleaving protease) activity and propose the pathogenetic events underlying this unusual association.The patient was admitted to our hospital because of anemia (hemoglobin level 7.8 g/dl, mean cell volume 90 fl, reticulocyte count was 12%) and thrombocytopenia (platelet count 124 × 10 3 /mm 3 ). Other laboratory findings were: serum aptoglobin <8 mg/dl, lactate dehydrogenase 1,733 UI/l, and alkaline phosphatase 603 UI/l.…”
mentioning
confidence: 98%
“…However, these and other investigations (gastroscopy, mammography, and bronchoscopy) could not document any primary neoplastic lesion. A diagnosis of TTP secondary to occult adenocarcinoma diffusely metastatic to bone marrow was established, but a few days later the patient died.Only a few cases of TTP secondary to metastatic adenocarcinoma are known in the literature [2][3][4][5][6][7]. The mechanism of secondary TTP is different from the idiopathic mechanism.…”
mentioning
confidence: 99%
See 2 more Smart Citations